The Effect of Social Support on Clean and Healthy Life Behavior in Fishing Communities in Karampuang Village, Mamuju Regency - Sri Ayuningsih; Yusriani; Fairus Prihatin Idris (Institute of Computer Science (IOCS), 2022)
Conditions of Clean and Healthy Living Behavior (PHBS) in Indonesia still have many problems that require efforts to change unhealthy behaviors into healthy ones, one of which is through the Clean and Healthy Behavior program. With the demographic transition and disease epidemiology, limited information, knowledge, and socio-cultural and lifestyle changes related to behavior tend to be increasingly complex. IKS coverage in West Sulawesi Province is still low at only 14.5% as well as in Mamuju Regency at 13%. In Karampuang Village 86 (Healthy Families), 467 (Pre-Healthy Families), and 200 (Unhealthy Families). The research was conducted with the aim of determining the effect of social support on PHBS in fishing communities in Karampuang Village, Mamuju District, and Mamuju Regency. This research is quantitative research, analytical descriptive with a cross-sectional approach. The sample is women/housewives of productive age between 19-45 years and has children under five, with the main livelihood of family members being fishermen, with a total sample of 176 respondents. Methods of data collection are done by using a questionnaire. Furthermore, editing, coding, entry, cleaning, and tabulating data are carried out. Then the data is processed using a computer in the IBM SPSS Statistics 21 program. The results showed that Social Support affected clean and healthy living behavior with a p-value of 0.004. In conclusion, the process of achieving a clean and healthy life is strongly influenced by the support provided by the husband. Family support has an important role because the family can encourage both physically and mentally for mothers to carry out clean and healthy living behaviors. It is better if the social support factor is further improved, especially the support from the family in this case the husband as well as from the village government and the surrounding community